Isolation and Total Synthesis of Kirkamide, an Aminocyclitol from an Obligate Leaf Nodule Symbiont1. (1st June 2015) - Sieber, Simon; Carlier, Aurélien; Neuburger, Markus; Grabenweger, Giselher; Eberl, Leo; Gademann, Karl
Abstract The new C7N aminocyclitol kirkamide (1) was isolated from leaf nodules of the plant Psychotria kirkii by using a genome‐driven 1H NMR‐guided fractionation approach. The structure and absolute configuration were elucidated by HRMS, NMR, and single‐crystal X‐ray crystallography. An enantioselective total synthesis was developed, which delivered kirkamide (1) on a gram scale in 11 steps and features a Ferrier carbocyclization and a Pd‐mediated hydroxymethylation. We propose that kirkamide is synthesized by Candidatus Burkholderia kirkii, the obligate leaf symbiont of Psychotria kirkii. Kirkamide (1) was shown to be toxic to aquatic arthropods and insects, thus suggesting that bacterial secondary metabolites play a protective role in the Psychotria/Burkholderia leaf nodule symbiosis.